2013
DOI: 10.2106/jbjs.l.00046
|View full text |Cite
|
Sign up to set email alerts
|

Level of Evidence: Does It Change the Rate of Publication and Time to Publication of American Academy of Orthopaedic Surgeons Presentations?

Abstract: The LOE of AAOS presentations is positively related to rate of publication and inversely related to time to publication. Presentations with higher levels of evidence are published in the peer-reviewed literature at a greater and faster rate than those with lower levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 18 publications
3
38
1
Order By: Relevance
“…Donegen et al [7] reported that AAOS presentations have only a 49% publication rate in peer-reviewed journals after 5 years. Voleti et al [28] found that at 5 years. 72% of Level I and II presentations and 46% of Level III and IV presentations were published.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Donegen et al [7] reported that AAOS presentations have only a 49% publication rate in peer-reviewed journals after 5 years. Voleti et al [28] found that at 5 years. 72% of Level I and II presentations and 46% of Level III and IV presentations were published.…”
Section: Discussionmentioning
confidence: 95%
“…This would suggest that the proportion of high-quality publications will further increase with time. However, when translated to number of publications, this represented 44 high-quality articles and 105 lesser-quality papers [28]. publications in the pediatric orthopaedic subspecialty [4].…”
Section: Discussionmentioning
confidence: 99%
“…The publication rate of presentations at the AAOS meetings was assessed for the time periods 1990–1992, 1993, 1996, and 2001. The publication rates of presentations over those time periods were respectively reported as 46%, 44%, 34%, and 49% (Voleti et al 2013; Bhandari et al 2002; Hamlet et al 1997; Murrey et al 1999). The publication rate of presentations at the Society of Military Orthopaedic Surgeons meetings from 1999 to 2003 was reported as 44% (Fuller et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards the eligibility assessments were crosschecked. All included studies have been described using following criteria: type of study (multi-center vs. single-center vs. case report), type of data collection (prospective vs. retrospective), level of evidence (assessment using the Journal of Bone and Joint Surgery ranking system) [24], patient cohort (number of patients who underwent TAR, number of replaced ankles), ankle prosthesis type used in the mentioned study, and the follow-up duration. We used the score of Coleman et al [6,22] (commonly known as the Coleman Methodology Score (CMS)), which has been modified by Gougoulias et al [10] to assess the quality including patients who underwent TAR.…”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%